Patient age at diagnosis is associated with the molecular characteristics of diffuse large B-cell lymphoma. - Klapper, W.; Kreuz, M.; Kohler, C. W.; Burkhardt, B.; Szczepanowski, M.; Salaverria, I.; Hummel, M.; Loeffler, M.; Pellissery, S.; Woessmann, W.; Schwanen, C.; Trumper, L.; et al. (Blood, 2012)
Diffuse large B-cell lymphoma is the most frequent type of B-cell lymphoma in adult patients but also occurs in children. Patients are currently assigned to therapy regimens based on arbitrarily chosen age limits only (eg, 18 or 60 years) and not biologically justified limits. A total of 364 diffuse large B-cell lymphomas and related mature aggressive B-cell lymphomas other than Burkitt lymphoma from all age groups were analyzed by comprehensive molecular profiling. The probability of several biologic features previously reported to be associated with poor prognosis in diffuse large B-cell lymphoma, such as ABC subtype, BCL2 expression, or cytogenetic complexity, increases with age at diagnosis. Similarly, various genetic features, such as IRF4 translocations, gains in 1q21, 18q21, 7p22, and 7q21, as well as changes in 3q27, including gains and translocations affecting the BCL6 locus, are significantly associated with patient age, but no cut-offs between age groups could be defined. If age was incorporated in multivariate analyses, genetic complexity lost its prognostic significance, whereas the prognostic impact of ABC subtype and age were additive. Our data indicate that aging is a major determinant of lymphoma biology. They challenge current concepts regarding both prognostic biomarkers and treatment stratification based on strict age cut-offs.
Keywords: Adolescent; Adult; Age Factors; Analysis of Variance; Antineoplastic Combined Chemotherapy Protocols/therapeutic use; *Chromosome Aberrations; Comparative Genomic Hybridization; DNA-Binding Proteins/genetics/metabolism; Enhancer of Zeste Homolog 2 Protein; *Gene Expression Profiling; *Gene Expression Regulation, Leukemic; Humans; Immunohistochemistry; In Situ Hybridization, Fluorescence; Linear Models; Lymphoma, Large B-Cell, Diffuse/diagnosis/drug therapy/*genetics; Middle Aged; Mutation; Outcome Assessment, Health Care/methods; Polycomb Repressive Complex 2; Prognosis; Proto-Oncogene Proteins c-bcl-2/genetics/metabolism; Proto-Oncogene Proteins c-bcl-6; Transcription Factors/genetics/metabolism; Young Adult